Relação Cálcio/Fósforo Disponível em Rações para Tilápia do Nilo (Oreochromis niloticus) - de Miranda, E. C.; Pezzato, Antonio Celso [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Graner, C. F.; Rosa, G. J.; Pinto, LGQ (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2000)
The objective of this work was to evaluate the effect of Ca: available P (P-a) ratio in the diets on performance and bone mineral depositions of juvenile Nile tilapia (2.5 +/- 0.5g). Seven isoproteic and isoenergetic diets (28% CP and 3100 Kcal of DE/Kg of diet), with similar crude fiber and sulfur aminoacids content, were used. The diets had 0.50 and 0.25; 0.50 and 0.50; 0.50 and 0.75; 0.80 and 0.40; 0.80 and 0.80; and 0.80 and 1.20% of Ca and P-a which corresponded to Ca/P-a ratios of 2:1;1:1 and 1:1.5, respectively. An additional control diet, with low levels of Ca and Pa (0.02 and 0.12%, respectively) was used. A completely randomized design with a 2'3 factorial arrangement (Ca level and Ca:P-a ratio) on treatments, plus the additional control diet and three replications was used. Five fishes per aquaria were randomly allotted to 21 fiberglass aquaria (80L). The temperature of the water was maintained close to 26degreesC, and the oxygen, pH and ammonia levels of the water were monitored. The results showed that it was necessary a minimum dietary level of 0.25% of P-a for a satisfactory bone mineral depositions, and that the best performance results were achieved using diets with Ca: P-a ratios between 1:1 and 1:1.5.
Availability of calcium: phosphorus ratio in diets for Nile tilapia (Oreochromis niloticus)
Keywords: bony and carcass mineral deposition; calcium : available phosphorus ratio; Oreochromis niloticus; performance